In Situ Synthesis of Palladium Nanoparticles in Polymer Brushes Followed by QCM‐D Coupled with Spectroscopic Ellipsometry. (21st August 2013) - Koenig, Meike; Rodenhausen, Keith Brian; Schmidt, Daniel; Eichhorn, Klaus‐Jochen; Schubert, Mathias; Stamm, Manfred; Uhlmann, Petra
<x xml:space="preserve">Abstract</x> The combinatorial method of quartz crystal microbalance coupled with spectroscopic ellipsometry can be used to follow the in situ synthesis of catalytically active palladium nanoparticles in polymer brushes in situ. By combining these two orthogonal techniques, it is possible to thoroughly characterize the thickness, composition, optical, and mechanical properties of nanoscopic thin films. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>